(untitled) (Journal of Economic Research & Business Administration, 2016)
Human resources are characterized by the system of indicators, re flecting the processes of reproduction of the population, their ability to meet the needs of life under the circumstances, given the state of health, safety and the environment. Nowadays the development of human re sources is relevant for our country. Indicators of education, culture and health reflect the performance and quality of human resources. Forma tion and development of human resources are particular important as they represent the real factor in economic growth and special link of national wealth. Human resources include indicators that provide well-being and comfort of living. The reproduction of human resources expended con siderable funds annually, including the cost of operation of the system of upbringing, education, health promotion and other factors increase the performance of people, increasing the working time and other aspects of the favorable conditions for life. This, in turn, leads to an increase of labor productivity growth and living standards.